Drivers of vulnerability to climate change in the southernmost region of Bahia (Brazil) - Neves, Frederico Monteiro; Alvarez, Guineverre; Corrêa, Fábio Fernandes; Silva, João Batista Lopes (Sociedade & Natureza, 2021)
The region that comprises the Atlantic Forest is one of the most degraded areas of the planet, being especially vulnerable in climate change scenarios, which project a mean temperature increase between 2ºC and 3ºC by 2070 for the Brazilian Northeast region. This article aims to analyze the main drivers of socio-environmental vulnerability in the Atlantic Forest region that comprises the southernmost identity territory of Bahia (Brazil) and their potential consequences for coping with climate change. To this end, historical data on land use and occupation was spatialized and evaluated, along with socioeconomic indicators and legal environmental adequacy in the municipalities that make up this territory. The results indicate four structural drivers that generate regional vulnerabilities: the persistence of deforestation; the continuous expansion of monoculture areas; the maintenance of low levels of well-being of the population; as well as a picture of legal environmental liabilities. Based on the analysis of these data, strategies are proposed to increase the adaptive capacity to climate change in this region, especially considering the role of municipalities as a central actor in the implementation of adaptation actions by incorporating into their existing planning instruments indicators and strategies that address the multiple current challenges, especially when the federal government seems to be neglecting climate change.